Osteogenic potential of stem cells‐seeded bioactive nanocomposite scaffolds: A comparative study between human mesenchymal stem cells derived from bone, umbilical cord Wharton's jelly, and adipose tissue. Issue 1 (15th November 2016) - Kargozar, Saeid; Mozafari, Masoud; Hashemian, Seyed Jafar; Brouki Milan, Peiman; Hamzehlou, Sepideh; Soleimani, Mansooreh; Joghataei, Mohammad Taghi; Gholipourmalekabadi, Mazaher; Korourian, Alireza; Mousavizadeh, Kazem; Seifalian, Alexander M.
Abstract: Bone regeneration is considered as an unmet clinical need, the aim of this study is to investigate the osteogenic potential of three different mesenchymal stem cells (MSCs) derived from human bone marrow (BM‐MSCs), umbilical cord Wharton's jelly (UC‐MSCs), and adipose (AD‐MSCs) seeded on a recently developed nanocomposite scaffold (bioactive glass/gelatin) implanted in rat animal models with critical size calvarial defects. In this study, after isolation, culture, and characterization, the MSCs were expanded and seeded on the scaffolds for in vitro and in vivo studies. The adhesion, proliferation, and viability of the cells on the scaffolds evaluated in vitro, showed that the scaffolds were biocompatible for further examinations. In order to evaluate the scaffolds in vivo, rat animal models with critical size calvarial defects were randomly categorized in four groups and treated with the scaffolds. The animals were sacrificed at the time points of 4 and 12 weeks of post‐implantation, bone healing process were investigated. The histological and immunohistological observations showed ( p < 0.01) higher osteogenesis capacity in the group treated with BM‐MSCs/scaffolds compared to the other groups. However, the formation of new angiogenesis was evidently higher in the defects filled with UC‐MSCs/scaffolds. This preliminary study provides promising data for further clinical trials. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 61–72, 2018.